The ACAMTO study—impact of add-on osteopathic treatment on adolescent patients with anorexia nervosa: study protocol for a randomized controlled trial - Aurélie Letranchant (BMC, 2021)
Abstract Background Anorexia nervosa (AN) mainly affects women (sex ratio 1/10) and most often starts during adolescence. The prognosis of AN remains poor (10% of deaths and high risk of chronicity). Body dissatisfaction, disturbances in recognition and identification of body sensations are some of the key symptoms of AN. However, there is a contrast between this consensual observation of body image disorders in AN, and the relative deficit of specifically targeted body treatments. Our proposal for a body approach specifically dedicated to AN is based on the understanding that posture, breathing, muscle tension and body perception are closely linked to our psychological and emotional state and are therefore disturbed in patients with AN. The purpose of this monocentric randomized controlled trial is to evaluate if a targeted osteopathic protocol treatment for AN in addition to treatment as usual (TAU) is significantly more effective than TAU alone. Methods In total, 72 patients meeting the inclusion criteria will be randomly assigned to one of the two treatment groups: one receiving the specific osteopathic treatment targeted for AN in addition to the TAU (group A) and the other one, receiving TAU only (group B). The patients in group A will receive 5 30-min osteopathic treatment sessions. Soft specific palpatory techniques on the diaphragm, digestive system and cervical region will be performed. The TAU is defined by the multidisciplinary approach recommended by the French health high authority. The primary outcome is the evaluation of interoceptive sensibility and secondary outcomes include clinical and psychopathology-related symptoms with assessment of somatic dysfunctions’ evolution. A qualitative study will also be carried out, applying the Interpretative Phenomenological Analysis method. Patients will be included for a maximum of 14 weeks between the inclusion time and the last evaluation. Discussion If the results of the study are positive (statistically significant efficacy of this osteopathic treatment protocol), the study will provide arguments in favor of osteopathic sessions as a possible non-invasive additional treatment option in the multidisciplinary care approach for patients with AN. Trial registration ClinicalTrials.gov ID: NCT04666415 , Release Date: December 11, 2020; N° ID-RCB: 2019-A02613-54.